Layered Operation Optimization Methods for Concentrated Solar Power (CSP) Technology and Multi-Energy Flow Coupling Systems - Chunchao Wu; Yonghong Zhao; Wulin Li; Jianjun Fan; Haixiang Xu; Dingkun Yuan; Zhongqian Ling (Energies)
Solar energy is an abundant renewable resource; the energy reaching the Earth from sunlight in just one hour exceeds the annual energy consumption of all humankind. Concentrated solar power (CSP), as a grid-friendly clean energy utilization method, has unique development advantages. The CSP system can be equipped with relatively mature, low-cost, large-capacity thermal energy storage, ensuring stable and controllable power generation. As the low-carbon economy progresses, the coupling between electricity, heat, and gas systems is increasing. The traditional energy supply system, which uses electric heating separation and layered scheduling for distribution networks, makes it difficult to fully exploit the network resources and achieve globally optimal operation strategies. The principle and the main components of centralized solar power (CSP) generation technology are introduced, and a layered optimization method suitable for a multi-energy flow coupling system is discussed, which can realize collaboration between CSP and other renewable energy sources better and improve the operation efficiency and flexibility of the whole energy supply system.